Formation and electronic properties of palladium hydrides and palladium-rhodium dihydride alloys under pressure - Xiao Yang (Nature Portfolio, 2017)
Abstract We present the formation possibility for Pd-hydrides and Pd-Rh hydrides system by density functional theory (DFT) in high pressure upto 50 GPa. Calculation confirmed that PdH2 in face-centered cubic (fcc) structure is not stable under compression that will decomposition to fcc-PdH and H2. But it can be formed under high pressure while the palladium is involved in the reaction. We also indicate a probably reason why PdH2 can not be synthesised in experiment due to PdH is most favourite to be formed in Pd and H2 environment from ambient to higher pressure. With Rh doped, the Pd-Rh dihydrides are stabilized in fcc structure for 25% and 75% doping and in tetragonal structure for 50% doping, and can be formed from Pd, Rh and H2 at high pressure. The electronic structural study on fcc type Pd x Rh1−xH2 indicates the electronic and structural transition from metallic to semi-metallic as Pd increased from x = 0 to 1.